Analytical solution for cauchy reaction-diffusion problems by homotopy perturbation method - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak (Penerbit UKM, 2010)
In this paper, the homotopy-perturbation method (HPM) is applied to obtain approximate analytical solutions for the Cauchy reaction-diffusion problems. HPM yields solutions in convergent series forms with easily computable terms. The HPM is tested for several examples. Comparisons of the results obtained by the HPM with that obtained by the Adomian decomposition method (ADM), homotopy analysis method (HAM) and the exact solutions show the efficiency of HPM.